Analisa Yuridis Pelanggaran Administrasi Dalam Perkawinan Poligami. (Studi Kasus : Putusan No 158/Pdt.G/2024/PTA.Bdg) - Hadi, Fajri Setiyo; Fattinudin, Muhammad (Postulat, 2025)
This study aims to provide a legal analysis of the practice of polygamy based on the Compilation of Islamic Law (KHI) and Marriage Law in Indonesia and its impact on population control. Polygamy in Indonesia is regulated in the KHI, and men who wish to practice polygamy must meet certain requirements, such as obtaining permission from the first wife or the court. However, in practice, violations of these rules often occur and cause legal and administrative problems. This study uses a qualitative method approach by reviewing various laws and regulations, court decisions, and related literature. Interviews were also conducted with lawyers, population administration officers, and polygamists. The research findings show that although the KHI and the Marriage Law provide a clear legal framework for polygamy, their implementation often encounters obstacles in practice. Polygamy is often carried out without proper procedures, such as without the permission of the first wife or court approval. This gives rise to various legal problems, including administrative sanctions and legal uncertainty for wives and children who practice polygamy. In addition, violations of polygamy regulations also have implications for population control. In many cases, the status of polygamous marriages is not properly recorded on population documents such as family cards or birth certificates. This causes difficulties in family management and civil rights. The study calls for stricter prosecution of polygamy violations, greater legal involvement of the community, and a population control system to ensure that all marriages are properly registered and family rights are protected.